Firms’ Attributes and Environmental Disclosure: Evidence from Listed Firms in Bangladesh - Chowdhury, Md. Ali Arshad; Dey, Mouri; Abedin, Md. Thasinul (Asian Journal of Accounting Perspectives, 2020)
Research aim: This paper aims at finding out the quality of environmental reporting and its association with company characteristics considering listed companies from various sectors through the lens of legitimacy theory and stakeholder theory in Bangladesh. Design/ Methodology/ Approach: Secondary data relevant to company characteristics and environmental disclosure have been collected from various parts of the annual reports of firms for the year 2016. This study considers one dependent variable breaking down into three levels and four independent variables. Level of environmental disclosure (LED) is the dependent variable while size, profitability, leverage and industry type are independent variables. Research finding: By employing Ordinary Least Square (OLS), the level of environmental disclosures (LED-1) is significantly associated with firm size, unlike the profitability, leverage and production attributes. The moderate disclosure level (LED-2) is likely to be affected by the firm size, unlike the other factors. Furthermore, the greatest disclosure level (LED-3) is to be strongly affected by business size and profitability. Moreover, the study confirms that firm type has no impact on environmental disclosure. Theoretical contribution/ Originality: This paper provides insights into the quality of environmental disclosure of Bangladeshi companies. It reveals that only leverage and size affect the total environmental disclosure of firms, unlike type and other features. This has a perfect alignment with the legitimacy theory that larger firms tend to disclose more to legitimise their activities and scale up their image. Practitioner/ Policy implication: This paper helps firms in implementing environmental disclosure policies and make them more environmentally responsible. Limitation/ Implication: Exploring the qualitative environmental disclosures among various types of industries in Bangladesh in a longitudinal manner by addressing more control variables may contribute to future research on determinants of corporate environmental reporting. Keywords: Environmental Disclosure, Company Characteristics, Bangladesh Type of article: Research paper JEL Classification: C01, C21